Analisa Produk Skincare Pria Ditinjau dari Perspektif Maqoshid Syariah - Deshilma, Ayufa; Wulansari, Rika (Indonesian Journal of Islamic Economics and Business, 2022)
Skincare men are products that can help treat or protect men's skin. This paper aims to analyze the product guarana & coffee energizing moisturizer skincare men from an Islamic perspective and provide a view using the maqoshid sharia perspective. This might describe and divide the maqoshid perspective into five categories, they are religion, self, intellect, family and wealth. A qualitative approach with content analysis was used in this study to analyze the connectivity between guarana & coffee energizing moisturizer skincare men and maqoshid products. The results of this study try to describe men's skin care into five maqoshid namely religion, soul, mind, lineage and property as products that bring maslahah. Skincare that contains skincare harm that is suitable for our skin and can overcome our skin problems.